Prevalence of vitamin B12 deficiency in type 2 diabetes mellitus patients on metformin therapy in a tertiary care hospital - A., Gomathi; K., Keerthiga (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The objective of the study was to estimate the prevalence of vitamin B12 deficiency and presence of peripheral neuropathy in type 2 diabetes patients on metformin treatment. Methods: This cross-sectional study was carried out in Department of Biochemistry and Medicine in a tertiary care teaching hospital in south India. Type 2 diabetes mellitus patients diagnosed based on World Health Organization (WHO) criteria treated with metformin for more than 6 months were included in the study. B12 levels were estimated and DNS scoring, vibration perception test and 10 gm Semmes-Weinstein monofilament test done. Results: A total of 55 participants were identified. Most of them were on 1500 mg of metformin once a day in divided dose. In this study maximum number of participants are in the age group of 50-70 years. Peripheral neuropathy is seen in 43.9% of persons with normal B12 levels and 28.5% of persons with low B12 levels. A Chi square test showed a chi square statistic value of 1.8221 with a p value of 0.312 which is not significant. Univariate analysis showed vitamin B12 deficient patients are of significantly higher age (63 years versus 57 years p=0.01) and with higher duration of treatment (9 years versus 6 years p=0.01). Conclusions: Prolonged metformin therapy is associated with deficiency of vitamin B12. The prevalence of B12 deficiency among diabetic patients on metformin was found to be 25.45%. Routine B12 estimation and correction of low B12 levels will be beneficial to these patients. Earlier initiation of B12 in patients on metformin may prevent the onset of neurological damage.